Involuntary resettlement in development projects policy guidelines in World Bank-financed projects - Cernea, Michael M. (World Bank e-Library., 1988)
Development projects sometimes require that people be involuntarily resttled from areas where they live and work to other locations. Adequate policy and purposive implementation are necessary to minimize and reverse the negative effects of compulsory relocation on individuals and the economy, and to help people become reestablished on a productive, self-sustainble basis. This paper addresses the policy issues and operational implications of development projects that cause involuntary resettlement. The general principles for resettlement as planned change are discussed, with emphasis on government responsibility, involvement of resettlers in the choice among available resettlement options, and prevention of adverse impact in host populations and the environment. The operational procedures described in the paper are tailored to each of the different stages of the project cycle in World Bank financed projects.